DETERMINANTS OF GREEN SUKUK INVESTMENT IN INDONESIA - oktaviana, Ulfi kartika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The Green Sukuk program has facilitated money flows for sustainable future development. Green Sukuk represents a successful national collaborative initiative aimed at combating climate change. Since the sukuk offering period, conditions have demonstrated heightened demand, reflecting significant investor interest in the Green Sukuk market. This article aims to examine the significance of environmental incentive in investing decisions within the Indonesian Green Sukuk market. A literature analysis revealed that while investors in the Green Sukuk market regard the attributes of Green Sukuk as significant, they do not disregard profit considerations.